Effectiveness of application of Helichrysum italicum essential oil in wound healing: report of 3 cases - Wijayadi, Linda Julianti; Pratiwi, Dian (Institute Of Computer Science (IOCS), 2024)
Helichrysum italicum (Hi) essential oil is commonly used in wound healing. Hi is an option for treating acute wounds, especially bleeding wounds. Coconut oil has also long been used for various skin disorders including wound healing and microbial infections. The high amount of antioxidants will be useful against free radicals which are considered the main cause of inflammation during the wound healing process. Hi essential oil was chosen because of its antimicrobial, anti-inflammatory, and wound-healing activities, all of which supported the wound-healing process in the three patients in this case report. The purpose of this case report is to determine the effectiveness of using Hi essential oil in healing wounds. We report 3 patients with wounds treated with topical Hi 10% essential oil in virgin coconut oil (VCO) applied three times daily until healed. All cases showed good wound healing without secondary infection. Despite the irritating side effects in patient 2, all three patients were satisfied with the results. The use of Hi 10% essential oil in VCO has advantages in terms of antimicrobial and anti-inflammatory effects on wound healing without secondary infection so it needs to be studied further as an alternative therapy option in wound healing